2008
DOI: 10.1128/aem.01234-08
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Association of Mycobacterium ulcerans with West African Predaceous Insects of the Family Belostomatidae

Abstract: A number of studies have suggested that Mycobacterium ulcerans, the etiological agent of Buruli ulcer, may be transmitted to humans by insect bites. M. ulcerans has been isolated from a predaceous aquatic insect, and PCR detection of M. ulcerans DNA in aquatic environments suggests that the organism is widely distributed within many invertebrate taxa and functional feeding groups. Thus, M. ulcerans may be concentrated through different trophic links. However, the specific environmental niche of M. ulcerans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 32 publications
(44 reference statements)
2
61
0
Order By: Relevance
“…The strains used in this study were WT M. ulcerans 1615 GFP (24) and an isogenic mycolactone-negative mutant, M. ulcerans 1615::TN118 GFP (24), and M. ulcerans V2 RFP, a fluorescently labeled clinical isolate from Australia (26). M. ulcerans 1615 GFP (ATCC 35840) is a well-characterized Malaysian human isolate with physical and biochemical properties very similar to those of the sequenced strain M. ulcerans Agy99 from Ghana (42).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strains used in this study were WT M. ulcerans 1615 GFP (24) and an isogenic mycolactone-negative mutant, M. ulcerans 1615::TN118 GFP (24), and M. ulcerans V2 RFP, a fluorescently labeled clinical isolate from Australia (26). M. ulcerans 1615 GFP (ATCC 35840) is a well-characterized Malaysian human isolate with physical and biochemical properties very similar to those of the sequenced strain M. ulcerans Agy99 from Ghana (42).…”
Section: Methodsmentioning
confidence: 99%
“…This strain produces neither the core nor the side chain of mycolactone, is not cytotoxic, and is avirulent. M. ulcerans strains were fluorescently labeled by introduction of a green fluorescent protein (GFP) or a red derivative (RFP) using the phage-integrating vector psm5 as described previously (24,44). By using this method, the GFP/RFP gene is inserted into the chromosome of M. ulcerans in the phage attachment site (att) and has no effect on the virulence of the bacterium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Random transposon mutagenesis has also revealed other genes necessary for toxin production. 30,31 Pidot et al 28 have shown that BU patients and persons that have been exposed to M. ulcerans, but who remain disease free, can make antibodies against several of the PKS enzymatic domains. On the other hand, it remains to be demonstrated if antibodies can access the synthases in bacteria to prevent toxin production and if this can prevent BU.…”
Section: Ulcerans Vaccine Targetsmentioning
confidence: 99%